Prevalence of gastrointestinal parasites of pigeons (Columba sp. Linnaeus, 1758) in three temples of Pokhara valley, Nepal - Gurung, Amrit; Subedi, Janak Raj (Journal of Natural History Museum, 2018)
The present study was conducted to determine the general prevalence, identification, compare area-wise as well as infection-wise prevalence and find out activities on health care of pigeon (Columba sp.) in three temples viz. Bhadrakali temple, Bindhyabasini temple and Tal Barahi temple of Pokhara valley. Iodine wet mount and different concentration technique (floatation and sedimentation) were used for faecal qualitative tests whereas verbally administered questionnaires for interview and Microsoft Excel and “R” software packages were used inanalyzing data. Out of 120 faecal samples collected by opportunistic random faecal sampling method examined, general prevalence rate of parasitic infection was 69.16%. Total of seven gastrointestinal parasites that includes one subclass of protozoan: Coccidia (19.16%) and six genera of helminths: Capillaria sp. (31.67%), Ascaridia sp. (21.66%), Echinostoma sp.(7.50%), Syangamus sp. (5.83%), Hymenolepis sp. (3.33%) and Hetarakis sp. (2.50%) were identified and reported first time in Nepal. The prevalence rates (55%) of helminths were higher than protozoan parasites (19.16%). The higher prevalence of gastrointestinal parasites was in Bhadrakali temple with 77.50% followed by Tal Barahi temple (72.50%) and lowest in Bindhyabasini temple (57.50%). Statistically, the difference in prevalence of gastrointestinal parasitic infection among study area was found to be insignificant whereas the difference in prevalence of single infection (43.83%) and mixed infections (25.83%) were also insignificant. No any activities on health care of pigeon regarding the gastrointestinal parasites were found. The study indicates that pigeons in three temples of Pokhara valley were highly susceptible to gastrointestinal parasites.